Nitrogen recycling by the gut microbiome in sarcopenia - Haller, Rosa; Hazia, Olha; Feldbacher, Nicole; Traub, Julia; Madl, Tobias; Habisch, Hansjörg; Horvath, Angela; Stadlbauer, Vanessa (Frontiers in Microbiology, 2026)
IntroductionSarcopenia, which is defined as loss of skeletal muscle mass and strength, affects up to 70% of patients with liver cirrhosis. Since hibernating animals maintain muscle mass through microbial nitrogen recycling, urease-producing bacteria may have a protective role in humans. We hypothesized that altered microbial urease abundance contributes to differences in nitrogen recycling potential between patients with and without sarcopenia, with sex-specific effects.MethodsStool samples from 152 patients with (n = 101) and without sarcopenia (n = 51) were analyzed. Functional profiles were predicted from 16S rRNA gene amplicon sequencing data using Tax4Fun2, and predicted abundances of urease subunit alpha were extracted. A systematic literature search identified 120 urease-producing taxa, of which 35 were represented in sequencing data.ResultsSarcopenia is associated with a lower predicted abundance of urease subunit alpha in patients with cirrhosis (n = 96; p = 0.045, r = 0.20; median = 0.0002 vs. 0.0004), irrespective of sex, and in women (n = 49, p = 0.037, r = 0.30, median = 0.0002 vs. 0.0004), irrespective of cirrhosis. Urease subunit alpha abundance increases with the use of proton pump inhibitors (PPIs) in the entire patient cohort (p = 0.0028, r = 0.24, median = 0.0003 vs. 0.0002), patients with cirrhosis (p = 0.033, r = 0.22, median = 0.0004 vs. 0.0002), and men (n = 103, p = 0.0005, r = 0.34, median = 0.0002 vs. 0.0001). Beta-blockers are associated with higher urease subunit alpha abundance in the entire patient cohort (p = 0.018, r = 0.19, median = 0.0003 vs. 0.0002) and women (p = 0.031, r = 0.31, median = 0.0004 vs. 0.0002). The overall abundance of potentially urease-producing taxa was comparable between the groups.DiscussionThe increased urease subunit alpha abundance in patients with liver cirrhosis and women without sarcopenia, and the influence of medication on abundance, point towards potential additional effects of beta-blockers in sarcopenia.